PEMANFAATAN PEKARANGAN RUMAH SEBAGAI STRATEGI PEMBERDAYAAN KETAHANAN PANGAN DI DESA GAYAM,KECAMATAN KENDAL KABUPATEN NGAWI JAWA TIMUR - Riska Fitri Laili Amalia, Erna; Farihy, Ahmad; Devita, Kartika; Ghoutsi Islahiyah Nurrohmah , Yanti; Taufiq, Amal (LPPM STAIMAS WONOGIRI, 2025)
This community empowerment activity by optimizing household yards aims to encourage people to actively manage their yards through cultivating vegetables, fruits, and medicinal plants to strengthen food security and maintain environmental sustainability. The program is implemented with an Asset-Based Community Development (ABCD) approach through five strategic stages: Discover, Dream, Design, Define, and Destiny. This method focuses on the utilization of assets, local potential, such as yard land, community expertise, local plant species, and social networks. The results of the community service show that success includes two aspects: first, at the activity process stage, which is shown by the enthusiasm and active participation of the community during the activity process, and second, after the activity process, with an increased understanding of the existence of assets they have, both physical assets such as home yards, plant seeds and various other tools in agriculture and non-physical assets, namely cooperation, organizations, social networks, and so on. Monitoring and evaluation are carried out to determine the condition of the community before the activity and the condition after the activity that shows a significant improvement.